KNOWLEDGE ATTITUDE AND PRACTICE REGARDING NEEDLE STICK INJURY AMONG NURSES IN THE TERTIARY CARE HOSPITAL OF LAHORE - AKRAM , S; MAQSOOD , A; NASAR , N; NAZ , M; MAQBOOL , N (Biological and Clinical Sciences Research Journal, 2024)
A Needle Stick Injury (NSI) occurs when a needle or other sharp object punctures the skin, potentially exposing the individual to blood-borne pathogens. Nurses are highly at risk of getting injured by sharp instruments. Objective: The study aims to assess nurses' knowledge, attitude, and practice regarding NSI and to find the correlation between these three parameters. Methods: This cross-sectional study was conducted at Sir Ganga Ram Hospital Lahore. In this study, 200 working nurses were included. A self-designed validated questionnaire was used. The software SPSS-23 was used to enter and analyze the data. Descriptive analysis was employed for summary statistics. Pearson’s correlation coefficient was used to investigate the relationship between variables. Results: Out of 200 nurses, 39 (19.5%) exhibited an experience of needle stick injury. A significant proportion (53.0%) of respondents were familiar with NSI, which causes wounds. Nurses have practices to utilize the hospital's resources to protect themselves from injuries. Significant relationships were found between all three domains (P<0.05).Conclusion: Based on these results, it is marked that while nurses possess an upright level of knowledge and show optimistic attitudes toward NSI prevention, to some extent, they require attention and improvement. Specific interventions and educational curricula are desirable to improve knowledge, attitudes, and practices, guaranteeing a better workplace, protecting healthcare personnel, and reducing the hazard of spreading blood-borne pathogens.